Exercise physiology 101: Part 128 - Foster, C. (1999)
Thoughts about strength training for skaters. For a skater, there are two primary purposes of strength training, stabilization and propulsion. The more important of the two is probably stabilization, since skating itself increases the strength and power of the propulsive muscles. The strength to hold their hips stable allows the push from the knee and hip extensors to be effective. In less accomplished skaters, lacking the strength to keep their hips stable, the skater falls off the push losing much of the effectiveness of their push. Thus, no matter how strong their hip and knee extensors are, they don't get very much into the push. Accordingly, the first priority in strength training is to develop hip stability. To develop hip stability, the main exercises needed are the so-called "core" exercises and total body exercises. A separate but related issue is how strength-power training interacts with endurance training. Several studies of combined strength-endurance training have demonstrated that endurance training hinders the development of strength. However, strength training doesn't seem to impair the development of endurance. Accordingly, if you are at a point in your training where improved strength-power is or primary importance, other training may have to be reduced temporarily. Recent experience with the national team has, however, demonstrated that maintenance strength-power training may be continued throughout the skating season on a 1-2 times per week basis.